Leadership Style in The Private Sector: Bibliometric Analysis - Amani, Akbar Riskal; Senen, Syamsul Hadi (Westscience Press, 2023)
Even though the private sector faces many challenges about human resources, there is still a dearth of literature on HR management methods in the private sector and private enterprise. The purpose of this research is to review the literature on private sector leadership style practices and how they affect other constructs. The Google Scholar database was chosen, and the publish or perish program was utilized to gather literature data.